Impact of Z-R relationship on flow estimates in central São Paulo - Calheiros, Roberto V. [UNESP]; Gomes, Ana M. [UNESP] (Int Assoc Hydrological Sciences, 2012)
Mean areal radar rainfall over catchments in the State of São Paulo is an operational product under development by the Meteorological Research Institute - IPMet. A pilot project is being carried out which focuses on the important Corumbatai River basin, under surveillance by the IPMet-operated Bauru radar. Previous work on the project explored the relative impact of factors like time resolution of radar data and reflectivity to rain-rate conversion relationships, when the relevance of the latter was verified. This paper deals with the stratification of those relationships by daily intervals and its impact on flow estimates. Daily values of radar mean rainfall using gauges and different conversion relationships are plotted against the corresponding flow at the basin outlet. Flow estimates derived by applying the rainfall from the different relationships to a previously obtained rainfall-runoff curve for the basin is compared to the historical hydrograph. Preliminary results suggest stratification has hydrological significance.
Keywords: areal radar rainfall; Z-R relationship; Corumbatai River basin; rainfall-runoff relationship